(untitled) (Iris Journal of Scholarship, 2019)
In this research article, I explore the effects that untapped potential has on students beyond their K-12 experience. Paying particular attention to have identity shapes people’s experience, I interviewed three participants that reflected on their K-12 experiences and the untapped potential they felt they left high school with.